2021
DOI: 10.1029/2020ja029035
|View full text |Cite
|
Sign up to set email alerts
|

3D Space‐Time Adaptive Hybrid Simulations of Magnetosheath High‐Speed Jets

Abstract: Many transient physical processes operate simultaneously and couple nonlinearly in the near-Earth environment across turbulent spatio-temporal scales, producing strong impacts on the cusp, magnetopause and ionosphere that are difficult to fully understand and predict without kinetic simulations. In particular, under quasi-radial interplanetary magnetic field (IMF) conditions the turbulent magnetosheath flow generates large-amplitude, spatially localized dynamic pressure enhancements, known as magnetosheath jet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 33 publications
4
48
0
Order By: Relevance
“…Magnetosheath jets are widely associated with the quasi‐parallel magnetosheath (Archer & Horbury, 2013; Němeček et al., 1998; Plaschke et al., 2013; Vuorinen et al., 2019), suggesting that their origin is tied to the interactions between the foreshock and the bow shock. Results from global hybrid simulations (Karimabadi et al., 2014; Omelchenko et al., 2021; Omidi et al., 2016; Palmroth, Hietala, et al., 2018) likewise point to foreshock–bow shock interaction as the origin of jets.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetosheath jets are widely associated with the quasi‐parallel magnetosheath (Archer & Horbury, 2013; Němeček et al., 1998; Plaschke et al., 2013; Vuorinen et al., 2019), suggesting that their origin is tied to the interactions between the foreshock and the bow shock. Results from global hybrid simulations (Karimabadi et al., 2014; Omelchenko et al., 2021; Omidi et al., 2016; Palmroth, Hietala, et al., 2018) likewise point to foreshock–bow shock interaction as the origin of jets.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a representative simulation cost of the hybrid global code HYPERS is ~1-million core-hrs for a 1-hour-long simulation of the Earth's magnetosphere [Y. Omelchenko, private communication], extrapolated from the simulations presented in Omelchenko et al (2021) for that specific resolution. As another example, the recent first 6D run of the hybrid global code Vlasiator cost ~15-million core-hrs for a 30-minutes-long simulation of the coupled solar wind-magnetosphere system using the Earth's dipole magnetic field [M. Palmroth, private communication].…”
Section: Discussion: System Science Of Global Magnetospheric Modelsmentioning
confidence: 99%
“…This is in part because MHD becomes problematic for thin boundary layers such as those at the bow shock and the magnetopause. Examples of beyond-MHD approaches at various stages of development include more-sophisticated fluid models (Wang et al, 2018), hybrid approaches that treat ions kinetically and electrons as a massless fluid (Karimabadi et al, 2014;Lin et al, 2017;Palmroth et al, 2018;Omelchenko et al, 2021), spectral methods (Koshkarov et al, 2021) and MHD models locally coupled with kinetic solvers (Daldorff et al, 2014;Chen et al, 2017). Global magnetospheric models are also becoming more complex in terms of the number of sub-systems that they include.…”
Section: Global Magnetospheric Modelsmentioning
confidence: 99%
“…They also suggested that the impact of IMF on jet formation and properties may be larger than has been thought. A recent 3D hybrid simulation study by Omelchenko et al (2021) supports this notion, as they linked the formation of jets to entangled fieldlines turbulently convecting in the magnetosheath, facilitating compression of solar wind plasma into jets. Some of these jets can make it to the magnetopause, and their high-dynamic pressure impacts on this boundary have been observed to cause many types of effects.…”
Section: 1029/2021ja029188 2 Of 19mentioning
confidence: 92%
“…A recent 3D hybrid simulation study by Omelchenko et al. (2021) supports this notion, as they linked the formation of jets to entangled field‐lines turbulently convecting in the magnetosheath, facilitating compression of solar wind plasma into jets.…”
Section: Introductionmentioning
confidence: 92%